Review of Ralph Locke. 2009. Musical Exoticism: Images and Reflections. Cambridge and New York: Cambridge University Press - Riggs, Kristy (Current Musicology, 2009)
Western artists, writers, and scholars have long used images to represent the exotic Other. In 1835, the French writer and poet Alphonse de Lamartine entitled his travelogue Souvenirs, impressions, pensees et paysages, pendant un voyage en Orient (1832-1833) ou, Notes d’un voyageur. A few years later, Franz Liszt unveiled his Album d’un voyageur (1837-1838) labeling the first book Impressions et poesies. Ralph Locke’s new book follows in a similar vein with the title Musical Exoticism: Images and Reflections. Just as travel to a foreign region conjured snapshots and images in the minds of Lamartine and Liszt, Locke uses impressions and observations to arouse curiosity and appreciation for musical representations of exoticism. The overarching goal of Musical Exoticism is to survey the ‘vast and varied repertoire of Western musical works that evoke exotic locales’. Locke presents his book as adding to and building on the growing body of music scholarship dedicated to examining the construction of the exotic Other. The opening chapters critique studies of exoticism and Orientalism – both music and otherwise. The overview brings together a wide variety of important scholarship. However, the majority of these studies-including several by Locke himself-focus on musical representations of a specific locale or people. Examples include studies of the alla turca style during the eighteenth century and the representation of Roma gypsy music in the early twentieth century. Because of the prevalence of such narrowly focused accounts of musical exoticism, Locke chooses to take a broader, more comprehensive perspective that seeks to examine exoticism throughout Western art music.